Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian (CV. Surya Perkasa Mandiri Malang) - Nanda Aris Pratama Aji; N. Rachma; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims the effect of price and promotion on purchasing decisions (CV. Surya Perkasa Mandiri Malang). The population in this study were all CV. Surya Perkasa Mandiri Malang. The sampling technique was calculated using the Slovin formula so that a sample of 70 respondents was obtained. The method of data collection in this study used a questionnaire. The results showed that simultaneously price and promotion had an effect on purchasing decisions. partially price and promotion have a positive and significant effect on the decision. Keywords: Price, promotion, consumer purchasing decisions